Mental disorders related to work in Alagoas: an epidemiological study between 2017 and 2021 (Research, Society and Development, 2023)
The aim of this study is to verify the epidemiological profile of cases of mental disorders associated with the work environment in the state of Alagoas between 2017 and 2021. This is a retrospective, descriptive, and observational epidemiological study with a conceptual and exploratory approach, whose analysis was based on data from 2017 to 2021, collected from the SINAN database available through DATASUS for the state in question. The data obtained were analyzed descriptively using Microsoft Excel 2019. The total number of individuals with mental disorders was 506, with 89.13% located in Maceió. 50.80% of the individuals were men, compared to 49.20% of affected women. The most frequent age range was between 28 and 47 years. The majority had neurotic disorders, stress-related and somatoform disorders, followed by 108 (21.34%) individuals with mood disorders. Of the total, 286 cases (56.52%) resulted in temporary disability for the individual, 7.70% of cases (39) required the issuance of a "Work Accident Communication", and 39.52% (200) were not reported to DATASUS. It was concluded that in Alagoas, during the period analyzed, cases were concentrated in Maceió, in the age range between 28 and 47 years. The highest prevalence occurs in male individuals, and the most frequent disorders are neurotic disorders, stress-related and somatoform disorders. The majority of cases resulted in temporary disability for the individual, without the need for a CAT issuance and with removal from the workplace.